From duty to right: The role of public education in the transition to aging societies - Yoshiaki Sugimoto; Masao Nakagawa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
This paper argues that currently advanced, aging economies experienced a qualitative change in the role of public education during the process of industrialization. In the early phases of the Industrial Revolution, public education was regarded as a duty that regulated child labor and thereby discouraged childbirth. As these economies developed and the population aged, younger generations came to view public education as a right, whereas older generations desirous of other public services became more politically influential. The eventual policy bias in favor of the elderly placed a heavier education burden on the young, inducing them to have fewer children. This vicious cycle between population aging and the undersupply of public education may have decelerated the growth of advanced economies in the last few decades.
Keywords: D70; H50; J10; J20; O40; 330; Compulsory Education; Generational Conflict; Fertility; Growth; Bildungspolitik; Alternde Bevölkerung; Fertilität; Generationengerechtigkeit; Wirtschaftswachstum; Theorie